ANALISIS PERBEDAAN PENDAPATAN PEDAGANG SEMBAKO SEBELUM SESUDAH BERGABUNG MITRA RUMAH PANGAN KITA KOTA KEDIRI - Faliana, Tara Indi; Kusumaningtyas, Dian; Bhirawa, Sigit Wisnu Setya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
This study analyzes income differences of grocery traders before and after becoming RPK partners in Kediri City. The method used is descriptive quantitative with a pretest-posttest one group design, involving 35 respondents selected via purposive sampling. The research model includes monthly income, education budget, and family burden variables. Instruments were tested for validity and reliability. The paired sample t-test showed a 10.46% average income increase, with p<0.05. A lower standard deviation indicates improved economic stability among partners. The RPK program effectively supports traders' welfare and strengthens sustainable food distribution.